2021
DOI: 10.1108/jibr-05-2020-0149
|View full text |Cite
|
Sign up to set email alerts
|

Do firm characteristics of concentrated ownership firms affect dividend payout beyond traditional motivations?

Abstract: Purpose This study aims to analyze the influence of firm characteristics in dividend payout in a concentrated ownership setting. Design/methodology/approach This study is probably the first to use the lasso technique for model selection and error prediction in the study of dividend payout in India. The lasso method comprises subsampling the available data set and performing reiterative regressions on those samples to generate the model with the best fit. This study incorporates four different ways of perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…An increasing but insignificant effect of investment (opportunities) ratio was observed for dividend payout policy in the present study of the listed manufacturing firms for the timeframe 2010-20. This insignificant impact of investment (opportunities) ratio for dividend payout policy is compatible with the conclusive evidence of (Jawade, 2021;Jeon, 2021;Lee & Lee, 2021). It is highly significant and the inverse effect of the life cycle ratio was observed for the dividend payout policy for the manufacturing industry of Pakistan.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…An increasing but insignificant effect of investment (opportunities) ratio was observed for dividend payout policy in the present study of the listed manufacturing firms for the timeframe 2010-20. This insignificant impact of investment (opportunities) ratio for dividend payout policy is compatible with the conclusive evidence of (Jawade, 2021;Jeon, 2021;Lee & Lee, 2021). It is highly significant and the inverse effect of the life cycle ratio was observed for the dividend payout policy for the manufacturing industry of Pakistan.…”
supporting
confidence: 77%
“…The studies related to dividends especially in the case of Pakistan conclude with some interesting discoveries. A study with a similar scope of dividend policy concluded that profitable firms tend to give dividends while the firm bearing a loss does not tend to give dividends in a similar manufacturing sector (Jawade, 2021). Accordingly, Kim et al, (2021) found that listed manufacturing firms, for setting their dividend payment, heavily depend on EPS and past DPS.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This study considers the extent of promoters' ownership by the proportion of equity shares held by promoters, i.e. shareholding (Mishra and Kapil, 2017; Jawade, 2021; Bhimavarapu et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%